A short‐term rural placement can change metropolitan medical students' knowledge of, and attitudes to, rural practice. Issue 2 (21st July 2014) - Wright, Julian R; Bourke, Lisa; Waite, Catherine J; Holden, Thom A; Goodwin, Jenni M; Marmo, Anne L; Wilson, Maxine L; Malcolm, Helen E; Pierce, David
Abstract: Objective: To determine whether a short‐term placement of metropolitan medical students in a rural environment can improve their knowledge of, and change their attitudes to, rural health issues. Design and participants: Medical students taking part in the March and May 2013 3‐week Rural Health Modules (RHMs) were invited to participate in focus groups and complete questionnaires before undertaking the RHM, after a 2‐day rural orientation and at the end of the RHM. Students were asked to comment on a range of issues affecting rural health care including their attitude to pursuing a rural career. Focus group transcripts were thematically analysed and questionnaire data were statistically analysed. Setting: The RHM is a 3‐week program designed and run by the University of Melbourne's Rural Health Academic Centre. Main outcome measures: Responses to questionnaire items from before and after completing the RHM, scored on a seven‐point Likert scale. Results: 69 of the 101 RHM students took part in this study. The focus groups identified five main themes in rural health care: access; teamwork, models of care and generalist practice; overlapping relationships; indigenous health; and working in a rural career. In all five areas, a change was seen in the depth of knowledge students had about these issues and in the students' attitudes towards rural health care. The questionnaires also showed a significant shift in the students' appreciation of, and positivity towards, rural health issues. Conclusion: Undertaking a 3‐week RHM changed students' perceptions of rural health and significantly improved their knowledge of issues facing rural health practitioners and patients.